Responses to alcohol and pregnancy policy pilot: Midwives’ views about proposals to manage risks associated with prenatal alcohol exposure - Fiona Woollard; Rebecca Brione; Rachel Arkell (Social Sciences and Humanities Open)
The Responses to Alcohol and Pregnancy Policy (RAPP) Project is a pilot study which seeks to address an evidence gap on midwives’ practice and views on mandatory recording of alcohol use during pregnancy, and transfer of this information to the child health record. The study aims to inform development of UK policy on the risks associated with prenatal alcohol exposure (PAE) and foetal alcohol spectrum disorders (FASD).The study sampled the views of qualified midwives currently working in the UK through an online survey and a small number of stakeholder interviews.Most respondents (82.79%) view recording information about alcohol use during pregnancy as already part of routine antenatal care. 96.9% were in favour of asking about alcohol consumption at the booking appointment, but 55.81% did not support asking questions about alcohol use at every appointment. A high percentage said that mandatory alcohol screening and transfer could have a negative effect on patients (over 80% in each case for feeling judged, guilt and shame), while just over half said they would have a negative effect on their role as a midwife: 52.88% for mandatory alcohol screening; 51.92% for transfer of information. We identified four interrelated themes in the qualitative data: Midwifery as a public health role; Barriers to Relationships, Practical Issues; and Consent and Rights.Our results and discussion highlight a lack of clarity about key concepts within current UK policy proposals. This leaves open the possibility that existing ideas about behaviour in pregnancy, risk and maternal responsibility will shape implementation.